Combustion Analysis of Ammonia/Oxygen Mixtures at Various Equivalence Ratio Conditions Using a Constant Volume Combustor with Sub-chamber - Bin Guo; Mitsuhisa Ichiyanagi; Makoto Horie; Keita Aihara; Takuma Ohashi; Abiyasu Zhang; Takashi Suzuki (Automotive Experiences, 2021)
The greenhouse effect issue is becoming more serious, and renewable energy is playing an increasingly important role. Among all alternative fuels, ammonia has been attracting attention as a carbon-free energy carrier for hydrogen, because of its large energy density per volume and easy storage and transportation. On the other hand, ammonia has a low combustion speed, which is an important issue for the use of ammonia as a vehicle fuel. To increase the mean flame speed of ammonia, the present study used the burned gas ejected from the sub-chamber for the compression of the mixture in the main chamber and the promotion of its HCCI combustion. Thus, the constant volume combustor with sub-chamber was used to realize the above combustion and to study the combustion characteristics of ammonia and oxygen mixture. In the experiments, initial pressure and initial temperature were unchanged and only the equivalence ratio was changed. The combustion pressure data were recorded and analyzed. As the result, the maximum combustion pressure (2.5 MPa) was obtained when the equivalence ratio was 0.4. The combustion speed was the fastest when the equivalence ratio was 0.6, and the mean flame speed was about 57.5 m/s.